Normal Schools and teacher training from Education for children with disabilities - Farid Rahme, Mônica María (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article discusses issues related to the training of teachers in the field of Brazilian special education. For this purpose, it takes data from the colonial period, from the early years of the Republic until today, when teacher training grants the challenge of specifying an education expected for everyone.To this end, the article explores, through bibliographic research, historical items related to teacher training in Brazil and its articulation with the education of students who have physical, motor, sensory, mental and/or cognitive characteristics. For the preparation of this paper, it is defended the hypothesis consisting of the establishment of educational institutions aimed to this public and the subsequent emergence of integration prospects and school inclusion led to the delineation of specific demands for the processes of initial teacher training, which are modified to the extent that changes occur in the orientation of educational policy. Finally, it briefly presents empirical research data on the theme of deficiency in the curricula of undergraduate courses at a public university located in the state of Minas Gerais. From the points discussed, it is intended to highlight the challenges in the training of teachers in an inclusive context and the need to structure formation processes that effectively articulate theory and practice.